Clinical and sociodemographic profile of asthma and attitude of parents towards inhaled corticosteroid use in children - Xavier, Gibi; Jose, O. (International Journal of Contemporary Pediatrics, 2024)
Background: To find out the clinical and socio demographic profile of asthma in 6–12-year-old children and also to understand the knowledge, attitude and practices of parents regarding the ICS use in a tertiary care centre, Alappuzha Kerala. Methods: Hospital based cross-sectional study, over a period of 1 year. Ethical committee clearance obtained. 141 children were selected from the asthma clinic, based on Inclusion and exclusion criteria. Questionnaire was given to parents, and methods of using MDI checked and corrected. Results: Most common reason for exacerbation of asthma are exposure to indoor air pollutants and viral infections. A major share of parents showing reluctance for using ICS due to fear of side effects. So usually using for a short course only, not as prescribed. Conclusions: The adherence of using ICS can be improved by parent-doctor communication and demonstrating the use of inhaler and its importance in asthma.